O direito como campo de gozo e o laço social - direito, pragmática e o discurso psicanalítico: uma crítica na razão jurídica - Rodrigues Filho, Walter (2007)
The scope of this thesis is to investigate about the contemporary law statute, articulating law and the psychoanalitic speeches in Freud and Lacan perspectives. Transformations that have been happenning in law since modernity, have inscribed ethical and epistemological problems that question its unity, legitimity and foundation. The theme is approached focusing the time problem. It s not about, however, a linear time, in a yesterday-today-tomorrow paradigm. It s about present time (in portuguese, tempo atual ): it s made of a discursive action, which is the action of how to operate and to say law, in a jouissance field. The different perspectives and discursive positions that constitute the juridical praxis determine the ex-centric effects,of no-sense, power effects. The speech is, in this context, analysed, which means that the different discursive positions of the subject of law science are read, constituting the juridical field around an emptiness that structures it and that is a condition for its social function. The pretentious scientism establishes different discourses, different ways of saying law; summarizing, it establishes the juridical speech as an unscientific (in portuguese, a-científico ) (it is about from object a of the lacanian notation, of a speech in which the alterity and the emptiness are constitutive). The psychoanalysis (that operates related to the subject of the science and inscribes the speech as a social bond, in the articulation between signifier and jouissance) was not used in a metaspeech function, which allowed it to be articulated to the pragmatics. It implied not in a criticism of the law, but a criticism in the juridical reason, considering that the different juridical speeches are constitutive of the juridical reason and of the truth of the subject that determines, in action, the way of saying law, producing social, economics and political consequences, that imply the subject, either for its actions and decisions (even when the subject places itself in a position of object - which is the condition of the subjective position changing, according to the analitical action premisses). In this context, a displacement of the traditional opositions, like humanities and natural science, closed system and open system was made. The unity of the juridical system, understood as an autopoietic system that is originated from its operations and, then, from the discoursives positions of the subject of law, one by one. A juridical system constitutively a-nomic, not because there would be lack of laws or norms, but for the effect of the norms and the discoursive ways of saying and operating law. Before that, the context of the well-saying ethics and of the lacanian (l)uhmannism (in an articulation between Luhmann and Lacan thoughts) was emphasized, and also the ex-sistence of the subject of law and its responsability for the act of citizen-ship (in portuguese, cidadani-a), which means, for the act of saying and reading the acts in law field, adopting a position before the strategies and effects of power that constitute the juridical speech. The legitimacy and foundation of law are not situated in traditional law philosophy, but they are inscribed in the functioning of democrac-y (in portuguese, democraci-a). The juridic-a-l philosophy is not opposed to knowing about law science, considering that it ex-sists in the act of operating law, inscribed in the not-knowing, which is constitutive of the juridical field